Risk analysis on different method of FFB evacuation: mechanical and conventional method at Jasin Lalang Estate / Mohd Azwan Mansor - Mansor, Mohd Azwan (Faculty of Plantation and Agrotechnology, 2019)
FFB evacuation process one of the important activity in oil palm plantation, but some plantation still choosing and using conventional method for loading even mechanical method are more efficient. Therefore, there are important for oil palm management and workers to know what the risk that might be occur during evacuation process. The risk during loading process can affect the productivity of oil palm. This research want to identify which method contribute the risk and method that suitable to be implement in their company. This research was carried out to know the risk of using the mechanical and conventional during FFB evacuation after the process of harvesting in oil palm plantation. The research was conducted at Jasin Lalang Estate with the total respondent is 30 sample. The data were analyzed by descriptive, multiple regression and T-test by using the Statistical Package for Science Social (SPSS) version 25. The result was showed that mechanical method contribute more risk than conventional method in term of quality of bunch and costing, while ergonomic problem contribute high risk to the conventional method. In conclusion, evacuation by using mechanical tractor grabber (MTG) contribute high risk during the loading process.